Assessing Impact of BRRI Released Modern Rice Varieties Adoption on Farmers’ Welfare in Bangladesh: Application of Panel Treatment Effect Model (Bangladesh Rice Journal, 2020)
This study assesses the impact of Bangladesh Rice Research Institute (BRRI) released modern wet (Aman) season rice variety adoption on farmers‟ well-being in Bangladesh. Bangladesh Integrated Household Survey (BIHS) data collected by IFPRI were used for this study. The study applied difference-in-difference treatment effect and difference-in-difference quantile treatment effect models using unbalanced panel data to achieve the set objectives. Analysis revealed that BRRI released wet (Aman) season rice technology has a robust and positive effect on small farmers‟ welfare in Bangladesh as indicated by the level of increases in per capita household real income, increases in real aman rice income, and also increases in yield and decreases both in poverty gap and squared poverty gap over time. The marginal and near landless farmers have not gained significantly through adopting BRRI released modern variety over non-adopters in terms of all the indicators except aman rice yield. However, only yield of BRRI released modern wet (Aman) season rice technology has positive and significant impact on the marginal and near landless farmers. As such, BRRI variety adoption seemed to be conducive in increasing the level of yield of marginal and near-landless farms but it hardly helps them to overcome the poverty level, unless other equity-enhancing policy measures are undertaken. Overall, there was large scope for enhancing adoption of BRRI released rice variety in order to reduce the poverty level in rural areas. The current rice policy (rice self-sufficiency) appears to be supportive to help Bangladesh rice sector for achieving food security in the country.Bangladesh Rice j. 2019, 23(1): 1-11